The mediating effect of e-health literacy on social support and behavioral decision-making on glycemic management in pregnant women with gestational diabetes: a cross-sectional study - Yumei, Peng; Huiying, Ke; Liqin, Shen; Xiaoshan, Zhao; Meijing, Zhao; Yaping, Xie; Huifen, Zhao (Frontiers in Public Health, 2024)
Background: Social support and e-health literacy are closely related to individual health behaviors, while behavior is premised on decision-making. Few studies have identified the relationships among social support, e-health literacy, and behavioral decision-making, and the nature of these relationships among pregnant women with gestational diabetes remains unclear. Therefore, this study aimed to investigate relationships among social support, e-health literacy, and glycemic management behavioral decisions in pregnant women with gestational diabetes. Methods: Using continuous sampling, an online cross-sectional survey was conducted among pregnant women with gestational diabetes who met the inclusion and exclusion criteria at four Class 3 hospitals in Fujian Province from October to December 2023. A structured questionnaire was used to collect data on general characteristics, socioeconomic status, social support, e-health literacy, and behavioral decision-making regarding glycemic management. Descriptive statistical analyses, correlation analyses, and mediation effects were used to assess associations. Results: A total of 219 pregnant women with gestational diabetes participated, and 217 valid results were obtained. The level of glycemic management behavior decision-making in women with gestational diabetes was positively correlated with e-health literacy (r = 0.741, P < 0.01) and with perceived social support (r = 0.755, P < 0.01). E-health literacy was positively correlated with perceived social support (r = 0.694, P < 0.01). The indirect effect of perceived social support on glycemic management behavior decisions through e-health literacy (a*b) was 0.153, accounting for 38% of the total effect. Conclusion:Social support and e-health literacy in pregnant women with gestational diabetes are related to behavioral decision-making in glycemic management. The results of this study provide a reference for developing targeted measures to improve glycemic management behaviors in pregnant women with gestational diabetes, which is crucial for achieving sustainable glycemic management.